2022
DOI: 10.31083/j.rcm2311370
|View full text |Cite
|
Sign up to set email alerts
|

Recent Evidence on Advances in PCI Treatment for Left Main Coronary Artery Disease

Abstract: Revascularization therapy significantly improves the outcomes of patients with left main coronary artery disease (LMCAD), compared with medical therapy alone. For many years, coronary artery bypass grafting (CABG) has been the primary and standard treatment strategy. However, with advances in percutaneous coronary intervention (PCI) techniques and improvements in patients' outcomes, there is growing evidence supporting PCI for LMCAD. In this review, we aim to integrate the available evidences on advances in PC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…Coronary artery disease (CAD) has become a global health problem, and coronary artery bypass grafting (CABG) remains an important treatment [ 1 ]. Postoperative new atrial fibrillation (POAF) is a commonly observed complication after CABG, and the incidence ranges between 28%–33% [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Coronary artery disease (CAD) has become a global health problem, and coronary artery bypass grafting (CABG) remains an important treatment [ 1 ]. Postoperative new atrial fibrillation (POAF) is a commonly observed complication after CABG, and the incidence ranges between 28%–33% [ 2 ].…”
Section: Introductionmentioning
confidence: 99%